Predicting Academic Performance through Time Management Skills and Academic Behaviors among University Students - Chhantel, Mamata (DAV Research Journal, 2026)
The purpose of the study is to analyze and identify the effects of the variables on academic performance by time-management skills, academic procrastination, study practices, and academic motivation among university students. The study has applied quantitative approach with descriptive and causal research design. Data were collected from 454 respondents from four different universities using five-point Likert scale. Convenience sampling technique was used while collecting the data. The SPSS software was used to perform the data analysis. The results show that routine management skills, study habits and academic motivation exert a strong positive impact on academic performance, and academic procrastination has a negative impact on academic performance. The study concludes that good time management habit, regular studying and academic motivation can enhance academic performance whereas procrastination of academic activities may reduce achievement. The study has put emphasis on the need to initiate systematic study schedules, motivation schemes and time management training in universities in order to improve academic success of the students in terms of higher education in Nepal.